Clinical-epidemiological profile of acute appendicitis at tertiary care institute of Bhuj, Kutch: a retrospective study - Vegad, Kamlesh; Parmar, Ghanshyam (International Surgery Journal, 2019)
Background: Acute appendicitis is one of the commonest surgical emergencies in all ages and the importance of specific elements in the clinical diagnosis remains controversial. Present study was performed with an aim to determine the presenting pattern of acute appendicitis and to review the pathological diagnosis. Methods: Present retrospective study was conducted in 115 patients who had appendicectomy for acute appendicitis at the Department of Surgery, tertiary care institute of Gujarat, India for the period of 1 year. The complaints and physical examination findings of the patients were obtained from their medical files Patient demographics, clinical features, operative findings and histology results were recorded on a special patient proforma. Results: Out of the total of 115 patients studied, 70 were males while 45 were females. The most common presenting complaints were abdominal pain (n=115), Nausea (n=55), vomiting (n=77) and diarrhoea (n=14). At surgery, 68.6% of appendices were apparently inflamed.1.7% were perforated and 5.2% had appendicular abscess whereas in 24.3% cases faecolith with inflammation was present. Sixty percent of the patients were discharged on the 4th day, 5.2% were discharged on 5th day, 4.3% on 6th day, 25.2% on 7th day and 3.4% on 8th day and 1.7% had a hospital stay of 10 or more days. Conclusions: Present study shows that acute appendicitis in India is a disease of young males. Hospitalization time was directly associated with the evolutionary phase and increased with the severity of appendicitis.